2018
DOI: 10.5194/acp-18-6887-2018
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental transport of biomass burning pollutants over the Mediterranean Basin during the summer 2014 ChArMEx-GLAM airborne campaign

Abstract: Abstract. The Gradient in Longitude of Atmospheric constituents above the Mediterranean basin (GLAM) campaign was set up in August 2014, as part of the Chemistry and Aerosol Mediterranean Experiment (ChArMEx) project. This campaign aimed to study the chemical variability of gaseous pollutants and aerosols in the troposphere along a west–east transect above the Mediterranean Basin (MB). In the present work, we focus on two biomass burning events detected at 5.4 and 9.7 km altitude above sea level (a.s.l.) over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 74 publications
2
14
0
1
Order By: Relevance
“…The northern and northeastern circulation types were responsible for Continental and Continental Polluted aerosols, since the air masses cross "the black triangle". Western and northwestern circulations were responsible for long-range transport of Smoke particles [49][50][51]. Southwestern circulations were mainly responsible for Dust particles and for Marine/Cloud aerosols.…”
Section: Aerosol Types Over Europementioning
confidence: 99%
See 1 more Smart Citation
“…The northern and northeastern circulation types were responsible for Continental and Continental Polluted aerosols, since the air masses cross "the black triangle". Western and northwestern circulations were responsible for long-range transport of Smoke particles [49][50][51]. Southwestern circulations were mainly responsible for Dust particles and for Marine/Cloud aerosols.…”
Section: Aerosol Types Over Europementioning
confidence: 99%
“…In addition, fire events were recorded in western, central, and northern Europe during 2011 and 2013-2018. Smoke particles of North American forest fire origin were reported over the Mediterranean Basin in 2013 [49,50] and 2014 [51], over western Europe in 2017 [56], over northern Europe in 2016 [55], and over central Europe in 2013 [47,52] and 2015 [53].…”
Section: Aerosol Types Over Europementioning
confidence: 99%
“…Previous long-term observations of the chemical composition of aerosol in the Mediterranean have shown that PM 10 (particulate mass with aerodynamic diameter less than 10 µm) is composed of secondary ammonium sulfate, primary and secondary organic aerosol from fossil fuels or biogenic origins, with contributions from natural aerosols from the Sahara and sea spray (Bove et al, 2016;Koulouri et al, 2008;Schembari et al, 2014;Calzolai et al, 2015). Mineral and sea salt contributions are significantly lower in PM 2.5 particle fraction (Querol et al, 2009a).…”
Section: Introductionmentioning
confidence: 98%
“…Positive matrix factorization (PMF; Paatero, 1997;Paatero and Tapper, 1994) has proved to be a useful statistical tool in identifying aerosol sources or ageing processes of organics. The source apportionment of PM 2.5 and PM 10 over the Mediterranean, from the PMF method, has been investigated in recent works and showed a large spatial variability in source contributions (Becagli et al, 2012(Becagli et al, , 2017Calzolai et al, 2015;Amato et al, 2016;Diapouli et al, 2017). The PMF approach was also used to study the aerosol source and ageing processes by utilizing the complex nature of organic aerosol in the Mediterranean (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biomass burning aerosol has frequently been observed over the basin, in particular the dry season in summer when forest fires are more common (Pace et al, 2005). Long-ranged plumes from north American fires have also been observed at high altitudes (Formenti et al, 2002;Ortiz-Amezcua et al, 2014;Brocchi et al, 2018;Ancellet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%